2009
DOI: 10.1136/thx.2009.116970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhaled mannitol, daily rhDNase and a combination of both in children with cystic fibrosis: a randomised trial

Abstract: Background: Osmotic agents, such as inhaled dry powder mannitol, may increase mucociliary clearance by rehydrating the airway surface liquid and thus act as disease-modifying treatments in cystic fibrosis (CF). This is the first therapeutic trial of inhaled mannitol in children with CF; it was compared with recombinant human deoxyribonuclease (rhDNase), the current best established mucolytic treatment. Methods: 38 children were recruited to an open crossover study. Subjects underwent an initial bronchial provo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 32 publications
1
82
6
Order By: Relevance
“…The additional benefit of mannitol over the study period was very similar in rhDNase users and nonusers when compared with control; this is in contrast with a recent, small phase II study [23], which suggested that the combined use of rhDNase and mannitol may not result in greater improvement than rhDNase alone. The present larger study demonstrated that mannitol offered an additional lung function benefit on top of rhDNase as part of standard therapy and confirms its applicability to a wide range of CF patients.…”
Section: Discussioncontrasting
confidence: 85%
“…The additional benefit of mannitol over the study period was very similar in rhDNase users and nonusers when compared with control; this is in contrast with a recent, small phase II study [23], which suggested that the combined use of rhDNase and mannitol may not result in greater improvement than rhDNase alone. The present larger study demonstrated that mannitol offered an additional lung function benefit on top of rhDNase as part of standard therapy and confirms its applicability to a wide range of CF patients.…”
Section: Discussioncontrasting
confidence: 85%
“…During 6 mo of double-blinded treatment, mannitol led to an average 7.3% improvement in FEV 1 compared to baseline ( p , 0.001), and a similar significant improvement when compared to placebo treatment ( p , 0.001). In contrast to data from a small study by Minasian et al (2010), patients using rhDNase with mannitol also showed lung function improvement (FEV 1 5.3%; p , 0.001), although this was numerically smaller than the FEV 1 change in those not using rhDNase (9.44% improvement from baseline). The effect of mannitol on pulmonary exacerbations appears to be smaller than that reported by Elkins et al (2006) in their study of HS.…”
Section: Targeting Asl Dehydration Via Osmotic Agentscontrasting
confidence: 48%
“…(30,31) The desirability of using nebulized mannitol is largely a result of its minimal airway transepithelial permeability, resulting in a longer duration of therapeutic action, as well as its pleasant taste and mouth feel for encouraging patient use. (32,33) Aerosolized Rienso particles were also captured on a TEM grid and analyzed to compare with the Rienso particles in the suspension. Image analysis of aerosolized Rienso particles by TEM demonstrated an overall pattern of monodispersed spherical particles, comprised of agglomerates of primary particles (Fig.…”
Section: Figmentioning
confidence: 99%